A circulating vaccine-derived poliovirus type 2 outbreak in a chronic conflict setting: a descriptive epidemiological study in South Sudan – 2020 to 2021 - Ayesheshem Ademe Tegegne; Atem Nathan Anyuon; George Awzenio Legge; Melisachew Adane Ferede; Zingbondo Isaac; Kirbak Anthony Laku; Sibhatu Biadgilign; Ochan Taban David Kilo; Fabian Ndenzako; Ndoutabe Modjirom; Olushayo Oluseun Olu; Sylvester Maleghemi (BMC Infectious Diseases, 2023)
Abstract Background In this study, we describe the epidemiological profile of an outbreak of the circulating Vaccine Derived Polio Virus type 2 in South Sudan from 2020 to 2021. Method We conducted a retrospective descriptive epidemiological study using data from the national polio/AFP surveillance database, the outbreak investigation reports, and the vaccination coverage survey databases stored at the national level. Results Between September 2020 and April 2021, 59 cases of the circulating virus were confirmed in the country, with 50 cases in 2020 and 9 cases in 2021. More cases were males (56%) under five (93%). The median age of the cases was 23.4 ± 11.9 months, ranging from 1 to 84 months. All states, with 28 out of the 80 counties, reported at least one case. Most of the cases (44, 75%) were reported from five states, namely Warrap (31%), Western Bahr el Ghazal (12%), Unity (12%), Central Equatoria (10%), and Jonglei (10%). Four counties accounted for 45.8% of the cases; these are Gogrial West with 12 (20%), Jur River with 5 (8.5%), Tonj North with 5 (8.5%), and Juba with 5 (8.5%) cases. The immunization history of the confirmed cases indicated that 14 (24%) of the affected children had never received any doses of oral polio or injectable vaccines either from routine or during supplemental immunization before the onset of paralysis, 17 (28.8%) had received 1 to 2 doses, while 28 (47.5%) had received 3 or more doses (Fig. 4). Two immunization campaigns and a mop-up were conducted with monovalent Oral Polio Vaccine type 2 in response to the outbreak, with administrative coverage of 91.1%, 99.1%, and 97% for the first, second, and mop-up rounds, respectively. Conclusion The emergence of the circulating vaccine-derived poliovirus outbreak in South Sudan was due to low population immunity, highlighting the need to improve the country’s routine and polio immunization campaign coverage.